Chemical diversity in angiosperms − monoterpene synthases control complex reactions that provide the precursors for ecologically and commercially important monoterpenoids - Srividya, Narayanan; Kim, Hoshin; Simone, Raugei; Lange, Bernd Markus (The Plant journal : for cell and molecular biology, 2024)
SUMMARY Monoterpene synthases (MTSs) catalyze the first committed step in the biosynthesis of monoterpenoids, a class of specialized metabolites with particularly high chemical diversity in angiosperms. In addition to accomplishing a rate enhancement, these enzymes manage the formation and turnover of highly reactive carbocation intermediates formed from a prenyl diphosphate substrate. At each step along the reaction path, a cationic intermediate can be subject to cyclization, migration of a proton, hydride, or alkyl group, or quenching to terminate the sequence. However, enzymatic control of ligand folding, stabilization of specific intermediates, and defined quenching chemistry can maintain the specificity for forming a signature product. This review article will discuss our current understanding of how angiosperm MTSs control the reaction environment. Such knowledge allows inferences about the origin and regulation of chemical diversity, which is pertinent for appreciating the role of monoterpenoids in plant ecology but also for aiding commercial efforts that harness the accumulation of these specialized metabolites for the food, cosmetic, and pharmaceutical industries. Significance Statement Terpenoids form the largest class of plant specialized metabolites and monoterpene synthases are enzymes that catalyze critical reactions that contribute to this chemical diversity. This foundational review provides an overview of the complex catalytic mechanism of these enzymes and discusses their relevance in the context of the roles of terpenoids in plant ecology and the food, cosmetic, and pharmaceutical industries.